2021
DOI: 10.1038/s41467-021-24742-0
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of the North Water ecosystem to climate change

Abstract: High Arctic ecosystems and Indigenous livelihoods are tightly linked and exposed to climate change, yet assessing their sensitivity requires a long-term perspective. Here, we assess the vulnerability of the North Water polynya, a unique seaice ecosystem that sustains the world’s northernmost Inuit communities and several keystone Arctic species. We reconstruct mid-to-late Holocene changes in sea ice, marine primary production, and little auk colony dynamics through multi-proxy analysis of marine and lake sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 64 publications
1
39
1
Order By: Relevance
“…Changes in sedimentary δ 15 N values have been used to successfully track bird colony sizes in Arctic (Michelutti et al, 2009;Yuan et al, 2010;Keatley et al, 2011;MacDonald et al, 2015;Davidson et al, 2018;Hargan et al, 2019;Ribeiro et al, 2021), Antarctic (Huang et al, 2014(Huang et al, , 2016Gao et al, 2018c;Yang et al, 2018), temperate (Stewart et al, 2015(Stewart et al, , 2019Hargan et al, 2018;Duda et al, 2020a,c), and tropical (Conroy et al, 2015;Wu et al, 2017aWu et al, , 2018 systems. Although this method is effective, Nie et al (2014b) suggested an improvement on δ 15 N as 15 N, which is calculated as the difference between acid-treated and untreated δ 15 N. The authors highlight that 15 N can track ornithogenic signals more effectively than δ 15 N in cold and arid environments that are subject to strong post-depositional processes such as guano deposition and ammonia-volatilization.…”
Section: Practically Unimpacted <0mentioning
confidence: 99%
“…Changes in sedimentary δ 15 N values have been used to successfully track bird colony sizes in Arctic (Michelutti et al, 2009;Yuan et al, 2010;Keatley et al, 2011;MacDonald et al, 2015;Davidson et al, 2018;Hargan et al, 2019;Ribeiro et al, 2021), Antarctic (Huang et al, 2014(Huang et al, , 2016Gao et al, 2018c;Yang et al, 2018), temperate (Stewart et al, 2015(Stewart et al, , 2019Hargan et al, 2018;Duda et al, 2020a,c), and tropical (Conroy et al, 2015;Wu et al, 2017aWu et al, , 2018 systems. Although this method is effective, Nie et al (2014b) suggested an improvement on δ 15 N as 15 N, which is calculated as the difference between acid-treated and untreated δ 15 N. The authors highlight that 15 N can track ornithogenic signals more effectively than δ 15 N in cold and arid environments that are subject to strong post-depositional processes such as guano deposition and ammonia-volatilization.…”
Section: Practically Unimpacted <0mentioning
confidence: 99%
“…Ribeiro et al, 2017;Limoges et al, 2018;Kumar et al, 2016;Detlef et al, 2021). Similarly, high values have been observed on the northwest Greenland shelf during the Holocene when climate conditions were favourable for high primary production (Limoges et al, 2020;Saini et al, 2020;Ribeiro et al, 2021). The modern fjord hydrography in Nuup Kangerlua has been shown to maintain productivity also in the outer fjord, as biomass and nutrients are partly advected from the inner fjord by currents and wind and tidal mixing, which, together with the warm, nutrient-rich waters carried by the WGC, can increase seasonal productivity (Juul-Pedersen et al, 2015).…”
Section: Records Of Marine Productivity In Nuup Kangerlua Since the L...mentioning
confidence: 86%
“…2020; Ribeiro et al . 2021; Koerner et al 2021) by adopting a multiproxy approach (physical properties, thin sections, grain size, quantitative mineralogy, pXRF) to provide an improved quantification of the sediment provenance and transport pathways in northwestern Baffin Bay since the last deglaciation, and their connection to regional climate history. This study provides more information about the long‐term development of the NOW, which is the largest and most productive polynya in the northern hemisphere on which local communities depend (e.g.…”
Section: Figmentioning
confidence: 99%